006.6 High prevalence of chlamydia and gonorrhoea among patients with genital ulcer disease in zimbabwe: potential implications for syndromic management. (13th September 2015) - Mungati, M; Mugurungi, O; Machiha, A; Tshimanga, M; Kilmarx, P; Nyakura, J; Shambira, G; Gonese, E; Herman-Roloff, A; Kupara, V; Lewis, D; Handsfield, H; et al.
Abstract : Background: Syndromic management of genital ulcer disease (GUD) as recommended by the Zimbabwe Ministry of Health and Child Care, includes antibiotics against Treponema pallidum (TP: benzathine penicillin), Haemophilus ducreyi (HD: erythromycin), and herpes simplex virus (HSV: acyclovir). However, these medications are not recommended to treat co-infections with Neisseria gonorrhoeae (NG: ceftriaxone or kanamycin) and Chlamydia trachomatis (CT: doxycycline or azithromycin) and, unless a person with GUD is simultaneously diagnosed with genital discharge syndromes (GDS), NG and CT co-infections will not be treated according to guidelines. Methods: In an ongoing study, we enrolled men and women with GDS or GUD syndromes in 6 clinics with high STI prevalence in Zimbabwe. In addition to testing ulcer secretions for TP, HD, and HSV by multiplex polymerase chain reaction (National Institute of Communicable Diseases, Johanneburg), all patients had urine (males) or vaginal swabs (females) tested for NG and CT by nucleic acid amplification (GeneXpert ® ). Results: To date, 302 patients have been enrolled for whom testing is complete, including 106 GUD and 196 GDS patients. NG and/or CT infections were present in 19/52 (36.5%) female GUD patients and 13/54 (24.1%) male GUD patients, compared to 26/96 (27.1%) female GDS patients and 68/100 (68.0%) male GDS patients. Of 32 GUD patients infected with NG (N = 24) and/or CT (N = 17), including 9 dual infections, only 4/18 (22%) of women and 4/14 (29%) of men met objective criteria for simultaneous GDS syndromic management. Conclusion: In our study, urethral or vaginal GC and/or CT infections were present in 30% of patients with GUD, of whom three quarters would not have been treated according to recommended syndromic treatment guidelines for sexually transmitted infections. Our study methods and findings should be relevant for Zimbabwe and other countries that are using a syndromic approach to STI control.